2020
DOI: 10.1186/s12885-020-07091-x
|View full text |Cite
|
Sign up to set email alerts
|

Sparing the hippocampus and the hypothalamic- pituitary region during whole brain radiotherapy: a volumetric modulated arc therapy planning study

Abstract: Background: Feasibility testing of a simultaneous sparing approach of hippocampus, hypothalamus and pituitary gland in patients undergoing whole-brain radiotherapy (WBRT) with and without a concomitant boost to metastatic sites. Introduction: Cognitive impairment and hormonal dysfunction are common side effects of cranial radiotherapy. A reduced dose application to the patho-physiologically involved functional brain areas, i.e. hippocampus, hypothalamus and pituitary gland, could reduce these common side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Nonetheless, the shape of the hippocampi contoured on CT scans fused with MRI was closer to the anatomical shape of the structure, particularly near the lateral ventricle and brainstem (Figure 6). The sizes and volumes of the hippocampi obtained in our study were similar to those reported in the literature [10,27,28] (length 4.5 cm, average width of body approximately 1 cm, mean hippocampal volume (delineated as dentate gyrus) for both LH and RH was 2.01 +/− 0.5 cm 3 ). A similar inter-observer study that analyzed variation in hippocampus delineation for PCI demonstrated that the greatest degree of delineation inaccuracy occurred in the posterior and anterior-medial borders (SD range 1-2.5 mm) on computed local shape variation [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nonetheless, the shape of the hippocampi contoured on CT scans fused with MRI was closer to the anatomical shape of the structure, particularly near the lateral ventricle and brainstem (Figure 6). The sizes and volumes of the hippocampi obtained in our study were similar to those reported in the literature [10,27,28] (length 4.5 cm, average width of body approximately 1 cm, mean hippocampal volume (delineated as dentate gyrus) for both LH and RH was 2.01 +/− 0.5 cm 3 ). A similar inter-observer study that analyzed variation in hippocampus delineation for PCI demonstrated that the greatest degree of delineation inaccuracy occurred in the posterior and anterior-medial borders (SD range 1-2.5 mm) on computed local shape variation [10].…”
Section: Discussionsupporting
confidence: 88%
“…Clearly, the last contoured cases showed the smallest degree of variation in hippocampal volumes. Marginally larger volumes of LH in comparison to RH obtained in our study are similar to data obtained from studies based on automated segmentation of the hippocampus [26,27]. The hippocampal outlines in the first three cases were characterized by a larger volume than in the other seven cases, which may be associated with the participants' uncertainty.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, together with the knowledge of CD after WBRT, awareness of neuroendocrine sequelae from the impaired hypothalamic-pituitary axis is growing [ 195 ]. Actually, the strong impact of irradiation on the hypothalamic-pituitary axis of pediatric subjects undergoing WBRT is well known but the possibility of a similar effect during WBRT for BM in adult subjects is recent [ 196 ]. In particular, there is a growing suspicion that acute hypothalamic dysfunction impairs the immune system’s ability to respond to infection and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…These studies should aim to: (i) evaluate in greater detail the cognitive effects and, more generally, the quality of life impairment during and immediately after WBRT; (ii) study the mechanisms producing these “early” effects; (iii) test in “clinical studies” advanced RT techniques based on both hippocampal-sparing and hypothalamic-pituitary-sparing, currently evaluated only in “planning studies” [ 196 , 199 , 200 , 201 ]; (iv) test new timings of antiglutamatergic drugs administration (e.g., start memantine a few weeks before WBRT), aimed at preventing not only late toxicity but also the acute effects; (v) compare stereotactic RT versus HA-WRT plus memantine based on data showing a reduced risk of CD in patients with 4–15 BMs treated with stereotactic RT compared to standard WBRT +/− memantine [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, P. Mehta and al [ 28 ]. reported, in a retrospective study, the importance of sparing the hippocampus and the hypothalamus during a whole brain radiotherapy, using a volumetric modulated arc therapy.…”
Section: Discussionmentioning
confidence: 99%